2011
DOI: 10.1002/jmri.22526
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of USPIO‐enhanced R2 imaging to dynamic blood volume changes in the rat kidney

Abstract: Purpose: To determine whether MRI in combination with an intravascular contrast agent is sensitive to pharmacologically induced vasodilation and vasoconstriction in the rat kidney.Materials and Methods: R 2 imaging was performed in 25 Sprague Dawley rats at 3 Tesla in the presence of ferumoxytol, an ultrasmall superparamagnetic iron oxide (USPIO) agent with a long plasma half-life. R 2 changes were measured following manipulation of blood volume by intravenous administration of adenosine, a short-acting vasodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 42 publications
2
36
1
Order By: Relevance
“…Changes in R 2 are potential confounders as demonstrated by recent report 34 because R 2 could change with compartmental volumes (tubular, vascular, and interstitial compartments), vasoactive drugs such as the ones used in this study could influence R 2 and, hence, R 2*. Interestingly, a previous report 35 indicated that L-NAME, which would be considered a vasoconstrictor, resulted in an increase in tubular volume and, therefore, in a decrease in R 2. On the basis of all the previously mentioned scenarios, the expected changes due to blood volume, hemoglobin, and R 2 may not only be non–dominant contributors, but their effects may actually be counteracting the large increases observed in R 2*.…”
Section: Discussionmentioning
confidence: 55%
“…Changes in R 2 are potential confounders as demonstrated by recent report 34 because R 2 could change with compartmental volumes (tubular, vascular, and interstitial compartments), vasoactive drugs such as the ones used in this study could influence R 2 and, hence, R 2*. Interestingly, a previous report 35 indicated that L-NAME, which would be considered a vasoconstrictor, resulted in an increase in tubular volume and, therefore, in a decrease in R 2. On the basis of all the previously mentioned scenarios, the expected changes due to blood volume, hemoglobin, and R 2 may not only be non–dominant contributors, but their effects may actually be counteracting the large increases observed in R 2*.…”
Section: Discussionmentioning
confidence: 55%
“…The dosage of the vasoactive drugs in this study was chosen based on a previously published animal study looking for blood volume changes by contrast enhanced MRI . During our initial testing, we observed little (less than 3%) cortical perfusion change (data not shown) with an adenosine dose rate of 0.5 mg/kg/min . Subsequently, we doubled the dose rate of adenosine to 1.0 mg/kg/min.…”
Section: Discussionmentioning
confidence: 99%
“…With proper kinetic analysis renal blood flow, glomerular filtration rate, total or capillary renal blood volume (or the volume of distribution) and plasma and tubular mean transit times may be assessed with these MR imaging [1215]. Intravascular iron-oxide agents can also be used to dynamically assess vascular changes following pharmacologic interventions [16] or assess the patency and architecture of the vasculature following renal transplants [17]. In the context of cancer imaging, iron-oxide or Gadolinium agents are also used to quantify (map) the mean vessel size and vascular architecture [18, 19].…”
Section: Assessment Of Renal Perfusion and Oxygenationmentioning
confidence: 99%